Partitioning of mesophyll conductance for CO2 into intercellular and cellular components using carbon isotope composition of cuticles from opposite leaf sides - Šantrůček, J; Schreiber, L; Macková, J; Vráblová, M; Květoň, J; Macek, P; Neuwirthová, J (Photosynthesis research, 2019)
We suggest a new technique for estimating the relative drawdown of CO2 concentration (c) in the intercellular air space (IAS) across hypostomatous leaves (expressed as the ratio cd/cb, where the indexes d and b denote the adaxial and abaxial edges, respectively, of IAS), based on the carbon isotope composition (δ13C) of leaf cuticular membranes (CMs), cuticular waxes (WXs) or epicuticular waxes (EWXs) isolated from opposite leaf sides. The relative drawdown in the intracellular liquid phase (i.e., the ratio cc/cbd, where cc and cbd stand for mean CO2 concentrations in chloroplasts and in the IAS), the fraction of intercellular resistance in the total mesophyll resistance (rIAS/rm), leaf thickness, and leaf mass per area (LMA) were also assessed. We show in a conceptual model that the upper (adaxial) side of a hypostomatous leaf should be enriched in 13C compared to the lower (abaxial) side. CM, WX, and/or EWX isolated from 40 hypostomatous C3 species were 13C depleted relative to bulk leaf tissue by 2.01-2.85‰. The difference in δ13C between the abaxial and adaxial leaf sides (δ13CAB - 13CAD, Δb-d), ranged from - 2.22 to + 0.71‰ (- 0.09 ± 0.54‰, mean ± SD) in CM and from - 7.95 to 0.89‰ (- 1.17 ± 1.40‰) in WX. In contrast, two tested amphistomatous species showed no significant Δb-d difference in WX. Δb-d correlated negatively with LMA and leaf thickness of hypostomatous leaves, which indicates that the mesophyll air space imposes a non-negligible resistance to CO2 diffusion. δ13C of EWX and 30-C aldehyde in WX reveal a stronger CO2 drawdown than bulk WX or CM. Mean values of cd/cb and cc/cbd were 0.90 ± 0.12 and 0.66 ± 0.11, respectively, across 14 investigated species in which wax was isolated and analyzed. The diffusion resistance of IAS contributed 20 ± 14% to total mesophyll resistance and reflects species-specific and environmentally-induced differences in leaf functional anatomy.
Keywords: Leaf mesophyll; extracelulární prostor; Carbon isotope discrimination; Leaf traits; Carbon Dioxide; Plant Leaves; mezofylové buňky; Extracellular Space; oxid uhličitý; Models, Biological; vosky; izotopy uhlíku; Altitude; Mesophyll conductance; Carbon Isotopes; Mesophyll Cells; Cuticle; Waxes; biologické modely; CO2 diffusion; nadmořská výška; listy rostlin